A Study on Factors Influencing Agriculture of Modern India . - Musale, Ramkisan (International Journal of Multidisciplinary Research and Studies, 2022)
Agriculture is the backbone of the Indian economy. However, it is going through the struggling phase marking sluggish or no growth for several decades. The Indian economy has been shifting its paradigm from core agriculture-based to service-oriented in the last few decades. It is influenced by global trends, market dynamics, government policies, and stakeholder expectations. After signing General Agreement on Tariffs and Trade in 1991, India accepted the ‘Open Door Policy.’ It further led to the major reforms in the Liberalization, Privatization, and Globalization (LPG) model. It positively impacts sectors like information technology, banking, finance, education, e-commerce, retail, insurance, and other service sectors. However, agriculture has remained detached from developments even after 70 years of independence.